E-Module of Science Development Based on Higher Order Thinking Skills on the Material of the Human Circulatory System for VIII Grade Students - Kuntarti Suhartini; Prasetyorini Prasetyorini; Indriyani Rachman (Jurnal Penelitian Pendidikan IPA, 2023)
Skills in thinking to solve every problem in the form of higher order thinking skills (HOTS) are competencies that must be possessed by 21st century students. HOTS for Indonesian students based on the analysis of PISA results is still considered very lacking, One of the efforts to improve students' HOTS, teaching materials are made in the form of HOTS-based electronic modules. The aim of this research is to develop an e-module based on HOTS, as well as to determine the effectiveness of the e-module being developed. This study uses a development that refers to the 4-D technique initiated by Thiagarajan namely define, design, develop, and disseminate. This research involved 35 grade VIII students of SMPN 2 Dramaga, selected using a purposive sampling technique. Data collection was carried out through HOTS tests and questionnaires. Analysis of research data using paired t-test and N-Gain test. The results of the analysis show that after the use of HOTS-based e-modules there is an increase in HOTS with N-Gain of 62% in the medium category. Testing the effectiveness of the e-module using a paired t-test showed a result of 0.000 which means that the HOTS-based e-module has a significant effect on increasing student HOTS.